2021
DOI: 10.1177/1745691620964076
|View full text |Cite
|
Sign up to set email alerts
|

Moral Reasoning Enables Developmental and Societal Change

Abstract: Moral reasoning is an essential part of how humans develop and a fundamental aspect of how human societies change over time. On a developmental timescale, reasoning about interpersonal disagreements and dilemmas spurs age-related changes in moral judgments from childhood to adulthood. When asked to distribute resources among others, even young children strive to balance competing concerns with equality, merit, and need. Over the course of development, reasoning and judgments about resource distribution and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 131 publications
(188 reference statements)
0
45
0
Order By: Relevance
“…To discuss policy recommendations, this review from developmental psychology will focus on children's group identity and adherence to group norms, which provide a window into children's motivations and intentions regarding social exclusion and bias (McGuire et al, 2015). The full scope of children's social cognitive abilities includes not only perceptions about group identity but also judgments about the fair and equal treatment of others, reflected by their developing moral cognition (Elenbaas, 2019; Killen & Dahl, 2021; Rutland et al, 2010).…”
Section: Promoting Fair and Just School Environments: Developing In...mentioning
confidence: 99%
“…To discuss policy recommendations, this review from developmental psychology will focus on children's group identity and adherence to group norms, which provide a window into children's motivations and intentions regarding social exclusion and bias (McGuire et al, 2015). The full scope of children's social cognitive abilities includes not only perceptions about group identity but also judgments about the fair and equal treatment of others, reflected by their developing moral cognition (Elenbaas, 2019; Killen & Dahl, 2021; Rutland et al, 2010).…”
Section: Promoting Fair and Just School Environments: Developing In...mentioning
confidence: 99%
“…While moral reasoning is a key factor for societal change (Killen and Dahl, 2021), the process of individual positioning is often shaped by empathy (Mathews and Collin-Vezina, 2016;Worthington et al, 2016). Thus, it is worthwhile to examine the role of empathy in the abolition of slavery and in the campaigns against animal production.…”
Section: The Role Of Empathymentioning
confidence: 99%
“…Early research in this tradition (Candee & Kohlberg, 1987) demonstrated that this could lead to rule breaking motivated by concerns about justice. In an era of social change, it is important to recognize that higher levels of moral reasoning can lead people not only toward personal development, but also toward support for social change to better achieve justice (Killen & Dahl, 2021).…”
Section: Legal Reasoningmentioning
confidence: 99%